Engineering abiotic stress tolerance via CRISPR/ Cas-mediated genome editing. (23rd October 2019) - Zafar, Syed Adeel; Zaidi, Syed Shan-e-Ali; Gaba, Yashika; Singla-Pareek, Sneh Lata; Dhankher, Om Parkash; Li, Xueyong; Mansoor, Shahid; Pareek, Ashwani
Abstract : Recent developments in genome editing tools have raised hopes for societal acceptance of genome-edited/modified crops. We present a critical evaluation of these tools in tackling abiotic stress, a highly complex and multigenic trait. Abstract: Abiotic stresses, including drought, salinity, temperature, and heavy metals, pose a major challenge for crop production and cause substantial yield reduction worldwide. Breeding tolerant cultivars against these abiotic stresses is the most sustainable and eco-friendly approach to cope with this challenge. Advances in genome editing technologies provide new opportunities for crop improvement by employing precision genome engineering for targeted crop traits. However, the selection of the candidate genes is critical for the success of achieving the desired traits. Broadly speaking, these genes could fall into two major categories, structural and regulatory genes. Structural genes encode proteins that provide stress tolerance directly, whereas regulatory genes act indirectly by controlling the expression of other genes involved in different cellular processes. Additionally, cis -regulatory sequences are also vital for achieving stress tolerance. We propose targeting of these regulatory and/or structural genes along with the cis -regulatory sequences via the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) system as a robust, efficient, and practical approach for developing crop varieties resilient to climate change. We also discuss the possibility of creating novel quantitative trait loci for abiotic stress tolerance via the CRISPR/Cas-mediated targeting of promoters. It is hoped that these genome editing tools will not only make a significant contribution towards raising novel plant types having tolerance to multiple abiotic stresses but will also aid in public acceptance of these products in years to come. This article is an attempt to critically evaluate the suitability of available tools and the target genes for obtaining plants with improved tolerance to abiotic stresses.